2011
DOI: 10.1155/2011/523596
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Induces Apoptotic Death in Murine Myelomonocytic Leukemia WEHI‐3 Cells In Vitro and Enhances Phagocytosis in Leukemia Mice In Vivo

Abstract: Emodin is one of major compounds in rhubarb (Rheum palmatum L.), a plant used as herbal medicine in Chinese population. Although many reports have shown that emodin exhibits anticancer activity in many tumor cell types, there is no available information addressing emodin-affected apoptotic responses in the murine leukemia cell line (WEHI-3) and modulation of the immune response in leukemia mice. We investigated that emodin induced cytotoxic effects in vitro and affected WEHI-3 cells in vivo. This study showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…In the present study, we demonstrated that the levels of cleaved caspase 3 fragments were elevated in emodin-treated HK-2 cells, which is consistent with previous studies (Wang et al, 2008(Wang et al, , 2007. These data suggested that caspase 3 plays a key role in emodin-induced apoptosis in HK-2 cells, even though caspase-independent pathway is involved in emodin-induced apoptosis in mice leukemia WEHI-3 cells (Chang et al, 2011). Caspase 3 is a critical and common executioner protease in apoptosis, and can be activated via two main signaling pathways: the death receptor-mediated extrinsic pathway and the mitochondria-mediated intrinsic pathway (Ashkenazi and Dixit, 1998;Green and Reed, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we demonstrated that the levels of cleaved caspase 3 fragments were elevated in emodin-treated HK-2 cells, which is consistent with previous studies (Wang et al, 2008(Wang et al, , 2007. These data suggested that caspase 3 plays a key role in emodin-induced apoptosis in HK-2 cells, even though caspase-independent pathway is involved in emodin-induced apoptosis in mice leukemia WEHI-3 cells (Chang et al, 2011). Caspase 3 is a critical and common executioner protease in apoptosis, and can be activated via two main signaling pathways: the death receptor-mediated extrinsic pathway and the mitochondria-mediated intrinsic pathway (Ashkenazi and Dixit, 1998;Green and Reed, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…The dose of particle (20 g/mouse) we used here has been selected from our previous study (Nemmar et al, 2009a) and is comparable to the doses employed in previous animal models of particulate air pollution exposure (Kido et al, 2011;Mutlu et al, 2007;Nemmar et al, 2011a). Emodin (1,3,8-trihydroxy-6-methyl-anthraquinone), an anthraquinone derivative from many herbs, is known to inhibit the production of inflammatory cytokines such as TNF␣, IL-6 and IL1␤ (Li et al, 2013;Xiao et al, 2014) and to have strong antioxidant and antiapoptotic actions Chang et al, 2011). In the present study, we elected to test emodin against DEP-induced lung toxicity, as the latter is associated with oxidative stress and inflammation (Nemmar et al, 2009a(Nemmar et al, , 2011a(Nemmar et al, , 2012b.…”
Section: Discussionmentioning
confidence: 99%
“…Emodin (1,3,8-trihydroxy-6-methyl-anthraquinone), an anthraquinone derivative from the Chinese herb Radix et Rhizoma Rhei, has been shown to have strong anticancer (Chang et al, 2011) http://dx.doi.org/10.1016/j.resp.2015.05.006 1569-9048/© 2015 Elsevier B.V. All rights reserved. and antioxidant activities Waly et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With overproduction of H 2 O 2 , concentration of both these enzymes decreases considerably, indicating that emodin induces apoptosis via the mitochondrial pathway [112]. Chang et al [113] showed that treatment with emodin can enhance phagocytic activity by monocytes and macrophages in the WEHI-3 leukemia murine model and also reduce liver and spleen weights. The potential of emodin to inhibit proliferation of K562 cell growth in vivo was shown by concomitant decrease in tumor volume and weight of xenografted tumor in nude mice.…”
Section: In Vivo Anti-cancer Effects Of Emodinmentioning
confidence: 99%